1980
DOI: 10.1056/nejm198005013021802
|View full text |Cite
|
Sign up to set email alerts
|

Physical Conditioning Augments the Fibrinolytic Response to Venous Occlusion in Healthy Adults

Abstract: The effects of a 10-week physical-conditioning program on fibrinolytic activity at rest and after stimulation by venous occlusion were studied in 69 healthy adults 25 to 69 years old. Physical conditioning was documented by treadmill performance, and fibrinolysis was measured with a newly developed radioenzymatic assay. Whereas fibrinolysis declined at rest from 16.2 +/- 1.3 to 11.4 +/- 0.8 units (mean +/- S.E.M.) (P = 0.0017), the increment in fibrinolysis produced by venous occlusion was increased from 21.7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
2

Year Published

1982
1982
2000
2000

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(29 citation statements)
references
References 31 publications
2
25
0
2
Order By: Relevance
“…9 Paffenbarger et al 3 42 suggest that this association cannot be explained by inherent physical attributes and that the exercise itself is responsible for the reduced risk. Regular exercise may influence coronary risk by altering plasma lipids.42 45 Plasma lipid levels are associated with risk for coronary heart disease,13-'7 and highly trained athletes tend to LDL cholesterol, and a 14.5% increase in triglycerides. The differences between men and women were statistically significant for each of the measures except LDL cholesterol, but the differences were no longer significant after adjusting for initial lipid values with an analysis of covariance.…”
Section: Discussionmentioning
confidence: 99%
“…9 Paffenbarger et al 3 42 suggest that this association cannot be explained by inherent physical attributes and that the exercise itself is responsible for the reduced risk. Regular exercise may influence coronary risk by altering plasma lipids.42 45 Plasma lipid levels are associated with risk for coronary heart disease,13-'7 and highly trained athletes tend to LDL cholesterol, and a 14.5% increase in triglycerides. The differences between men and women were statistically significant for each of the measures except LDL cholesterol, but the differences were no longer significant after adjusting for initial lipid values with an analysis of covariance.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise and catecholamine infusion studies (Cash and Allen, 1967;Schernthaner et al, 1983;Mant, Kappagoda and Quinlan, 1984;Small et al, 1984), show an acute response typified by increased fibrinolysis, FVIIIC, FVIIIRAg and platelet counts, but a variable platelet aggregation response. Both fitness (Williams et al, 1980) and age (Yokoyama BRITISH JOURNAL OF ANAESTHESIA et al, 1984) appear to modify these responses. The elderley and those with a history of myocardial infarction show an exaggerated platelet aggregation response to adrenaline (Schernthaner et al, 1983;Yokoyama et al, 1984).…”
Section: Neuroendocrine Response and Haemostasismentioning
confidence: 99%
“…Other studies revealed no alterations of the specific activity of fibrino gen in aging humans [12], Furthermore, the plasma fibrinogen concentration correlates with the plasma viscosity and is, therefore, seen as an independent risk factor of cardio vascular diseases [1], The prevention of cardiovascular risk fac tors is an epidemiologic challenge. Endurance training with an intensity of 50-70% of the maximal aerobic power has been shown to counteract the impairment of functional ca pacity and to retard the onset of pathological changes with age in both humans [13,14] and rats [4,15,16], In humans, acute physical activity does not influence the fibrinolytic sys 257 tem [17], but regular long-term activity in duces both hypercoagulation and increased fibrinolysis to keep the hemostasiologic bal ance on an elevated level [17,18]. The activa tion of fibrinolysis is related to the physical fitness [17,18].…”
Section: Discussionmentioning
confidence: 99%